A high efficiency biological system for treatment of coal gasification wastewater – a key in-depth technological research1. Issue 50 (4th June 2015) - Ji, Qinhong; Tabassum, Salma; Yu, Guangxin; Chu, Chunfeng; Zhang, Zhenjia
<x xml:space="preserve">Abstract</x> Wastewater treatment technology with a simple processing unit, easy management, low energy consumption, low sludge production and a cost of 0.135 per m3.